2005
DOI: 10.1007/s00268-005-7548-z
|View full text |Cite
|
Sign up to set email alerts
|

Marlex Mesh Prefix Plug Hernioplasty Retrospective Analysis of 865 Operations

Abstract: For 5 years (January 1998 to November 2002) our department has applied the Marlex Mesh Perfix Plug hernioplasty. This article demonstrates the experience gained in operative and postoperative aspects, costs, and outcome along with the results of a follow-up analysis. Altogether, 801 patients (749 males, 52 females) were operated on Sixty-four males had bilateral groin hernias, so the total number of hernioplasties amounted to 865. A total of 19 hernias were recurrent, 297 were direct, 545 were indirect or scro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…The current study had a number of limitations (e.g., the general belief that follow-up evaluation after hernia surgery must approximate 5 years) [11]. Pavlids [1] recently reported that the recurrence rate varies from 0% to 8% for laparoscopic repair and from 0% to 3.6% for open repair.…”
Section: Discussionmentioning
confidence: 99%
“…The current study had a number of limitations (e.g., the general belief that follow-up evaluation after hernia surgery must approximate 5 years) [11]. Pavlids [1] recently reported that the recurrence rate varies from 0% to 8% for laparoscopic repair and from 0% to 3.6% for open repair.…”
Section: Discussionmentioning
confidence: 99%
“…21 Many surgeons routinely use antibiotic prophylaxis during elective operations in order to reduce the risk of mesh infection. [22][23][24][25] Recently, however, the use of this pharmacological adjunct has been criticized. 26,27 The incidence of strangulated hernia varies significantly in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…1A, B; right) is used in approximately 80% of inguinal hernioplasties. 5,6 The Prolene (polypropylene) Hernia System (Ethicon, Inc) (Figs. 1A, B; left) is a newer 1-piece closure device that is made of a flat mesh connected by a 2-cm hollow mesh protrusion melded to a second flat mesh.…”
mentioning
confidence: 99%